Psychiatric morbidity, quality of life and marital satisfaction among spouse of men with opioid dependence syndrome: a study from North India - Soni, Ruchi; Upadhyay, Ritesh; Meena, Parth Singh; Jain, Mahendra (International Journal of Advances in Medicine, 2017)
Background: Opioid dependence syndrome has deleterious consequences not only on addict but also on the members of family especially his spouse who is most vulnerable to develop significant psychiatric disorder given the intimate nature of their relationship. Addressing these issues will be beneficial as spouses are important source of moral support and assistance to the substance user’s quest toward abstinence. Methods: For psychiatric morbidity, 100 spouses of men with opioid dependence syndrome were evaluated. Severity of opioid dependence in the husbands was assessed using severity of opioid dependence questioner (SODQ). Quality of life and marital satisfaction was assessed using short form health survey 36 (SF 36) and marital satisfaction scale (MSS) respectively. Results: Data analysis reveals that 33% of spouses had a psychiatric disorder. Primarily mood and anxiety disorder was present in 22% and 9% of subjects respectively. Highly significant difference existed between cases and controls in terms of marital satisfaction (p = 0.0001) and quality of life (p≤0.05) indicating low marital satisfaction and poor quality of life in spouses of opioid dependent individuals. Conclusions: Psychological distress and psychiatric morbidity in spouses of opioid dependent men is high, with poor quality of marital life and marital satisfaction being low. Hence, interventions that aim at allaying their distress and improving their mental health can improve the condition of the substance user and contribute to a better outcome of substance abuse treatment.